Study of Ukrainian Choir Music in the Process of Professional Training of Students from China - Martynenko, Ivan (Professional Art Education, 2021)
The purpose of the article is to article is devoted to the study of Ukrainian choral music by students from China in classes on choral conducting and choral class. Methodology. Important in the process of professional training of foreign students is the clarification of the content of education, aimed at considering the peculiarities of artistic mentality, the state of professional education, readiness for foreign students to perceive the content of education (it is reflected in work programs, curriculum, organizational and methodological support). The content of education aimed at preparing students to perform all the functions inherent in a modern teacher, strengthening the practical orientation of the content and forms of educational activities on the basis of a competency-based approach, ensuring a high level of independence of professional skills, creative activity of students, the organization of independent educational activities of Chinese students, aimed at their acquisition of additional knowledge, the ability to further self-improvement. The scientific novelty is that the purpose and tasks of the disciplines "choral conducting" and "choral class" are characterized; The peculiarities of educational work in these disciplines are considered, which are reflected in the individual form of education and should promote the formation of qualities that ensure the implementation of professional and pedagogical activities, as well as create the most favorable conditions for preparing foreign students to work with choirs. Results. Strengthening multifaceted ties with China is now one of Ukraine’s foreign policy priorities and has a lasting character. Among these connections, the most extensive are in the field of education. Today, students from the People’s Republic of China are perhaps the most significant part of foreign students in the country. The success of the partnership between Ukraine and China in the field of education is obvious, as evidenced by the mutual interests of young people in history, culture, traditions, developing cooperation between educational institutions of our countries, growing number of participants in youth exchange programs and more. The expansion of international contacts in all spheres of public life has led to human interest in the problems of intercultural communication. The dialogue of cultures allows its participants to express certain external information about the participants themselves, the internal emotional state, as well as the social statuses and social roles they play in relation to each other, which also confirms their "culture". Training programs in choral conducting and choral class are carried out on the repertoire, which belongs to different musical cultures, but the most significant array of works is represented by domestic choral art. Ukrainian choral culture is an invaluable treasure of national significance. For centuries, choral art has manifested itself as a true creation of the talent of the Ukrainian people, which embodied the integrity and, at the same time, the diversity of the inner world of past generations and has long been an organic part of human life. Conclusions. The issue of studying Ukrainian choral music by foreign students is important and requires considerable attention from teachers of choral conducting and leaders of student choirs. The study of Ukrainian choral music is based on a certain pedagogical experience of teachers and the principles of leading teachers of today. The variable nature of individual classes contributes to the professional development of foreign students. The study of Ukrainian choral music in choral conducting classes and choral class not only expands the musical worldview of students, develops their tastes and preferences, but also promotes the development of cultural dialogue between Ukraine and China.